Colostrinin: a proline-rich polypeptide complex of potential therapeutic interest - Janusz, M.; ZabÅ‚ocka, A. (Cellular and Molecular Biology, 2013)
A proline-rich polypeptide complex (PRP) subsequently known as ColostrininTM was found for the first time in ovine colostrum as a fraction accompanying colostral IgG2. Subsequently, similar polypeptides were found in human, bovine and caprine colostrum. PRP is a complex of peptides of molecular masses from 500 to 3000 Da. It contains 25% proline residues and 40% hydrophobic amino acids. It is not species specific, and is active both in vivo and in vitro. PRP possesses immunoregulatory properties, including effects on humoral and cellular immune responses, shows regulatory activity in Th1 and Th2 cytokine induction, and has the ability to inhibit the overproduction of reactive oxygen species and nitric oxide. PRP has also shown psychotropic properties. Both immunoregulatory and psychotropic properties suggest potential clinical use of PRP for neurodegenerative disorders. Beneficial effects of PRP/Colostrinin in the case of Alzheimer's disease were shown in double-blind placebo-controlled trials, in long-term open-label studies and in multicenter clinical trials. A very important property of PRP/Colostrinin and one of its components, a nonapeptide (NP), is the prevention of AÎ² aggregation and the disruption of aggregates already formed. Moreover, PRP has been found to modulate neurite outgrowth, suppress uncontrolled activation of cells, and reduce 4-HNE-mediated cellular damage. Biological response modifying activity of PRP/Colostrinin can play an important role in its use in the treatment of Alzheimer's disease and suggests its application beyond neurodegenerative disorders.